Pravna ureditev stavke de lege ferenda - Debelak, Marijan (Delavci in delodajalci, 2010)
In his contribution the author comments on some provisions of the Strike Act draft whereby his comments based both on the Constitution and international regulations. He approves of the broad definiton of the strike, acknowledges the solidarity strike yet opposes the provision according to which a strike is to be urgent, appropriate, as well as proportional. He further calls attention to some inconsistencies regarding the definition of strike organisers, the announcement of the strike and above all to inadequate approach regarding restrictions of the right to strike for the employees within the state and local government bodies, and within the public sector.
Keywords: delovna razmerja; pravna ureditev; sindikati; stavke; zaposleni